Factors influencing smallholder adoption of organic agriculture in Southeast geopolitical region of Nigeria - Ume, Chukwuma Otum; Onah, Ogochukwu Gabriella; Okpukpara, Benjamin Chiedozie; Chukwuma-Ume, Nice; Charles, Ukwuaba Ikenna; Omeje, Emmanuel Ejiofor; Chiemela, Chinedum Jachinma; Chituru, Ibe Justina; Orazulike, Ozioma (Frontiers in Sustainable Food Systems, 2023)
Introduction Organic Agriculture is considered one of the promising sustainable agricultural systems that can promote green economy measures, especially in developing countries where smallholder agriculture forms the backbone of the economy. With increasing awareness of the environmental and health benefits of organic foods, there has been an increasing number of studies assessing the demand side (determinants of consumers’ demand for organic products) within the global South. However, there is a dearth of research information on the supply side (e.g., factors influencing smallholder farmers’ willingness to engage in organic agriculture). To scale up organic agriculture among smallholder farmers, there is a need to explore and understand the factors influencing its adoption. Methods Using survey data from rural Nigeria, this paper applied Cragg’s double-hurdle model to assess the factors influencing smallholder farmers’ adoption of organic farming in the Southeast geopolitical region of Nigeria. Results The result showed that information about organic farming plays a major role in motivating farmers to adopt organic farming. Farmers that know what organic farming entails were found to be 1.31 percent more likely to adopt organic farming and to dedicate 1.23 percent more of their land to organic farming than the farmers that are less aware of organic farming. Similarly, an organized organic marketing structure and a premium on organic products were found to statistically improve the adoption of organic farming. The proportion of land dedicated to organic farming was found to be 2.15 percent more for farmers that received a premium for their organic produce than their counterparts that do not receive a premium for their produce. Discussion The findings demonstrated policy actions aimed at certification among smallholder farmers employing organic farming methods can facilitate system-wise organic farming in rural areas. However, the nature of such certification that will not jeopardize the agency of the farmers requires further investigation.